A new species of the diatom genus Campylodiscus (Bacillariophyta) from Dongtan, Chongming Island, China - Kociolek, Patrick; Wu, Bo; Liu, Qi; Wang, Quanxi (Phytotaxa, 2013)
A new species of genus Campylodiscus is described, Campylodiscus sinensis sp. nov., from Dongtan, Chongming Island, Shanghai, China. It is a small species compared with other species in genus Campylodiscus, with two characteristic kidney-shaped bumps externally and pyramidal verrucae. Light and scanning electron microscopy characteristics of this taxon support its systematic placement in the genus Campylodiscus. This new species is compared with other small species in genus Campylodiscus from around the world.